DAMPAK IMPLEMENTASI ZAKAT PRODUKTIF - Muh. Ruslan Abdullah (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2016)
Zakat is the third pillar of Islam that is considered to have a significant role in overcoming various economic problems, problems-problems are: 1. Unemployment, 2. Poverty , 3. Load the crisis and accounts payable, 4. The economy is bad, 5. Hoarding possessions. productive zakat is implemented in the form of venture capital assistance, resource assistance effort so that people can rise from the economic downturn. Distribution of zakat productively contributes greatly to the economy of poor community